2020
DOI: 10.1021/acssuschemeng.0c01832
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Catalyzed Glycerol Pretreatment of Sugarcane Bagasse: Understanding the Properties of Lignin and Its Effects on Enzymatic Hydrolysis

Abstract: In this study, lignin from acid-catalyzed glycerol (AG) pretreatment of sugarcane bagasse was recovered and characterized. Its effects on enzymatic hydrolysis and cellulase recycling were then investigated. Prior to lignin recovery, a two-step dilute acid and AG pretreatment was used to deconstruct sugarcane bagasse, which led to a glucan enzymatic digestibility of 99%, a glucose yield of 91%, and a xylose yield of 67%. Following enzymatic hydrolysis, lignin-rich residues were recovered by simple filtration at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…Acid-catalyzed glycerol (AG) pretreatment of sugarcane bagasse was investigated and it was found that glycerol had modified the bagasse lignin through α-etherification of β-aryl ethers and γ-esterification of hydroxycinnamic acids. The obtained lignin was highly hydrophilic, and it did not inhibit the enzymatic hydrolysis of pretreated bagasse (Hassanpour et al, 2020). By comparing liquid-hot-water (LHW) pretreatment with acid-free ethanolwater (EW) pretreatment, it was found that the nonproductive adsorption between EW pretreatment-induced lignin and cellulases was significantly weakened due to the advantages of suppressing the deposition of lignin condensates (Shi et al, 2018).…”
Section: Organosolv Pretreatmentmentioning
confidence: 99%
“…Acid-catalyzed glycerol (AG) pretreatment of sugarcane bagasse was investigated and it was found that glycerol had modified the bagasse lignin through α-etherification of β-aryl ethers and γ-esterification of hydroxycinnamic acids. The obtained lignin was highly hydrophilic, and it did not inhibit the enzymatic hydrolysis of pretreated bagasse (Hassanpour et al, 2020). By comparing liquid-hot-water (LHW) pretreatment with acid-free ethanolwater (EW) pretreatment, it was found that the nonproductive adsorption between EW pretreatment-induced lignin and cellulases was significantly weakened due to the advantages of suppressing the deposition of lignin condensates (Shi et al, 2018).…”
Section: Organosolv Pretreatmentmentioning
confidence: 99%
“…After, respectively, adding 2 g/L of two lignins, the glucan conversion of cellulose was increased from 28.0% to 37.4% and 31.3%. Hassanpour et al [ 108 ] prepared the acid–glycerol (AG) pretreated sugarcane bagasse and dilute acid pretreated sugarcane bagasse and recovered the lignin from enzymatic hydrolysis residual of AG pretreated sugarcane bagasse. After adding lignin produced from AG pretreated process to the two substrates, lignin did not inhibit the enzymatic hydrolysis efficiency of AG pretreated sugarcane bagasse, but increased the enzymatic hydrolysis efficiency of dilute acid pretreated sugarcane bagasse from 33 to 38%.…”
Section: Effect Of Introduced Lignin On Enzymatic Hydrolysismentioning
confidence: 99%
“…[ 312 ] Alternatively, lignin can be isolated from 2) a lignin‐rich residue by enzymatic digestion of residual polysaccharides or solubilization in organic solvents and subsequent precipitation by acidification from the concentrated residue. [ 313 ]…”
Section: Food Losses and Waste As Precursors Of Biocolloids And Advanced Bioplasticsmentioning
confidence: 99%
“…[312] Higher lignin yields have been achieved via acid-catalyzed glycerol treatment, enabling the recovery of 63% of the initial lignin in SCB at a high purity of 90%. [313] Lignin solutions can be transformed into nano-and microparticles by aerosolization or solvent exchange routes. [316] The size of lignin particles can be controlled by the processing conditions, [317] and their surface chemistry can be tailored by selecting the lignin source material.…”
Section: Isolation Of Polysaccharides and Polyphenolsmentioning
confidence: 99%